Systemic provocation in doxycycline induced fixed drug eruption: a case report - Niken Indrastuti, Anik Murwaningsih Rosmarini Estri Sih Hananti (Universitas Gadjah Mada, 2013)
Fixed drug eruption (FDE) is recurrent lesions that upon repeated uptake of causative drug, always appears at the same skin and mucosal site. Determination of causal relationship in drug allergy is very important. In this case report, cases of doxycycline-induced FDE was reported. The subject of the research was a 29-year-old male, referred by dermatologist, with history of reccurent FDE. Physical examination revealed an oval well demarcated patch hyperpigmentation. Patch test was perfomed on previous involved and uninvolved site. The result of the patch test was irrelevant. Retesting patch test gave similar result. Systemic provocation test or drug provocation test (DPT)Â with doxcycline were done with suspected drug under ambulatory survelance and gave positive result. In this case, the DPT succeeded to identify doxycycline as the causal agent of FDE. The work-up of a suspected drug hypersensitivity includes a detailed clinical history, physical examination, skin tests, and provocation tests. The DPT is recommended to confirm drugâs hypersensitivity reactions. Systemic provocation test is considered as the gold standard for diagnosing FDE.Keywords:Â Â fixed drug eruption - doxycycline - causal relationship - patch test - systemic provocation test